Impact of Board Structure on Performance of Listed Financing Sector in Sri Lanka - Balagobei, S; Anandasayanan, S (University of Jaffna, 2024)
Over recent years, corporate governance has become a major and highly contentious issue in all advanced economies, as well as in developing countries. Board size and composition constitute two of the most prevalent corporate governance factors, attracting wide theoretical attention. This paper examines the relationship between two of the most pertinent corporate governance factors that is, the size of the Board of Directors and the proportion of non-executive directors and firm performance on a sample of 19 listed companies from financial sector over the period 2008-2010. Our results reveal that board size and board composition significantly impact on ROE and Tobin's Q of the firms in financial sector. Further there is a negative relationship between the board size and firm performance but the positive relationship between board composition and the firm performance.
Keywords: Board composition; Corporate governance; Firm performance